2004
DOI: 10.3748/wjg.v10.i10.1487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of serum collected from rat perfused with compoundBiejiaruangandrug on hepatic stellate cells

Abstract: AIM:To observe the effect of compound Biejiaruangan decoction (CBJRGC) (composite prescription of Carapax trionycis for softening the liver) on proliferation, activation, excretion of collagen and cytokine of hepatic stellate cells (HSCs) and to find the mechanism of prevention and treatment of hepatic fibrosis by CBJRGC. METHODS:Using MTT, immunohistochemistry and image analysis technology, the related indexes for proliferation, activation, excretion of collagen and cytokine of hepatic stellate cells were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Moreover, Carapax trionycis may cause a decrease in the number of activated HSC and the total number of HSC [17]. These findings are in accord with our data and support the view that the antifibrotic effect of mYGJ is mainly mediated through regulation of HSCs proliferation and activation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Carapax trionycis may cause a decrease in the number of activated HSC and the total number of HSC [17]. These findings are in accord with our data and support the view that the antifibrotic effect of mYGJ is mainly mediated through regulation of HSCs proliferation and activation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our results showed that treatment with YPF‐P reduced the HYP content of lung and α‐SMA‐positive cells, and attenuated pathologic changes of PF. The BJRG compound select for reference drug can restrain the proliferation and activation of hepatic stellate cells, enhance the degradation of collagen and inhibit the expression of TGF‐β1 [35]…”
Section: Discussionmentioning
confidence: 99%
“…Also the hypotensive effect of rhynchophylline was observed (Song et al, 2000). We adopted the blood serum pharmacological method in our study (Guo et al, 2004) to take medicated serum as the drug source. This method could present the biotransformation in vivo and overcome confusion of other substances.…”
Section: Discussionmentioning
confidence: 99%